The Impact of SERVQUAL Dimensions on Customer Satisfaction in Education and Training: An Economic Perspective - Suryaman, Maman; Tukiran, Martinus (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the influence of the five SERVQUAL dimensions—tangible,  empathy, reliability, responsiveness, and assurance—on customer satisfaction in  education and training institutions using a Systematic Literature Review (SLR) approach.  The research aims to synthesize findings from empirical studies published between 2020  and 2024 to provide a comprehensive understanding of how these dimensions impact  customer satisfaction in this context. The review systematically collected and analyzed  relevant literature from reputable databases, including Dimention. A total of 9 studies  were selected based on predefined inclusion and exclusion criteria, ensuring that only  research focusing on SERVQUAL dimensions in education and training institutions and  their impact on customer satisfaction was included.The results reveal that all five  dimensions significantly contribute to customer satisfaction, with reliability and  assurance having the strongest impact. Tangible aspects, such as facilities and  infrastructure, and empathy, which reflects personalized attention, also play crucial roles.  Responsiveness, related to the promptness and willingness of service delivery, was found  to enhance trust and loyalty among customers. This study highlights the critical importance of implementing and improving  SERVQUAL dimensions to enhance service quality and satisfaction in education and  training institutions. The findings provide valuable insights for educators, policymakers,  and administrators to refine service delivery models and meet the growing expectations  of their customers.